Nutrition in infants under 6 months. Socioeconomic and cultural factors that influence it - Castro Villacres, Sixto; Costales de Arce, Laura; Ramírez de Paredes, Amelia (Revista Universidad de Guayaquil, 1988)
The loss of the habit of breastfeeding during the second half of the 20th century throughout the world constitutes a bisocial fact with incalculable projections for the future of humanity. Latin America is not capable of this modality; In this sense, the Ibero-American peoples follow the patterns of developed countries. During the 1970s, both researchers and national and international health authorities understood that the prevalence and duration of breastfeeding should be measured in population groups of different socioeconomic levels.